Secondary Caries in the Posterior Teeth of Patients Presenting to the Department of Operative Dentistry, Shahid Beheshti Dental School - Jaberi Ansari, Zahra; Valizadeh Haghi, Haleh (Journal of Dental School, 2019)
Objective: Secondary caries is a common problem in dental treatments and its occurrence is attributed to several factors. The present study aimed at assessing the prevalence of secondary caries in posterior teeth of patients presenting to the Department of Operative Dentistry, Shahid Beheshti Dental School. Methods: This descriptive study was conducted on 350 patients with 1,339 posterior teeth restored with amalgam or composite resin. Restorations older than 3 years were evaluated. Data regarding presence or absence of secondary caries, age of restoration, location of receiving dental care, tooth brushing technique and use of dental floss and mouthwash were recorded in a questionnaire. Statistical analysis was done using chi-square test. Results: The prevalence of secondary caries was 26% among the understudy patients. Mesio Ocluso Distal restorations (19.2%) had the highest prevalence of secondary caries. Composite restorations had higher prevalence of secondary caries compared to amalgam restorations (p=0.01). Teeth restored in private dental offices had a higher prevalence of secondary caries compared to those restored in university clinics (p=0.007). Patients who used mouthwash had a significantly lower prevalence of caries recurrence (p=0.05). Conclusion: The prevalence of secondary caries in patients presenting to the Department of Operative Dentistry of Shahid Beheshti Dental School was higher in the MOD restorations, composite restorations and teeth restored in private dental offices finally it was less in the patients using mouthwash.